Protein Purification Techniques A Practical Approach - Roe, Simon;Ed (Practical approach series, 244., 2001)
The protein purification Practical Approach books contain detailed practical information on the separation and purification of proteins. Protein Purification Techniques covers unit operations and analytical techniques in detail, while Protein Purification Applications has details of protein purification from a selected number of typical sources.